2007
DOI: 10.1271/bbb.70205
|View full text |Cite
|
Sign up to set email alerts
|

Action of Ascorbic Acid on a Myosin Molecule Derived from Carp

Abstract: The influence of L-ascorbic acid at 40 C incubation on the subfragment-1 and rod regions, prepared by chymotryptic digestion of myosin, and myosin was investigated by SDS-polyacrylamide gel electrophoresis and transmission electron microscopy respectively. It was observed that L-ascorbic acid acted more readily on the subfragment-1 region of myosin. Further, circular dichroism measurement indicated that L-ascorbic acid did not affect the structure of myosin. These results suggest that L-ascorbic acid acts more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Thus, they suggested a metal ion-free mechanism for generation of the semiquinone radical 16 , consisting of an initiation step involving a noncatalyzed oxidation of the phenolic substance 15 by oxygen to form superoxide anion, followed by a propagation stage involving oxidation of the phenolic substance by superoxide anion as illustrated in Figure 6 . The generation of superoxide anion and hydrogen peroxide is not unique to polyphenols, since even ascorbic acid undergoes such a reaction [ 54 ]. Tyihák et al [ 6 ] reported that the antimicrobial activity of phenolic substances such as cinnamic acid and transresveratrol depends on their generation of singlet oxygen, and this may involve reactions as depicted in Figure 6 .…”
Section: Singlet Oxygen Formation Via the Oxidation Of Phenolic Sumentioning
confidence: 99%
“…Thus, they suggested a metal ion-free mechanism for generation of the semiquinone radical 16 , consisting of an initiation step involving a noncatalyzed oxidation of the phenolic substance 15 by oxygen to form superoxide anion, followed by a propagation stage involving oxidation of the phenolic substance by superoxide anion as illustrated in Figure 6 . The generation of superoxide anion and hydrogen peroxide is not unique to polyphenols, since even ascorbic acid undergoes such a reaction [ 54 ]. Tyihák et al [ 6 ] reported that the antimicrobial activity of phenolic substances such as cinnamic acid and transresveratrol depends on their generation of singlet oxygen, and this may involve reactions as depicted in Figure 6 .…”
Section: Singlet Oxygen Formation Via the Oxidation Of Phenolic Sumentioning
confidence: 99%
“…Transition metal traces such as Fe 3+ can also be reduced to Fe 2+ and further react with H 2 O 2 through a Fenton mechanism . The resulting radicals may oxidize the sulfhydryl side chains into thiyl radicals­(S • ), promoting myosin II aggregation through S–S bonding. , In the presence of excessive V C , the oxidative radicals could be scavenged by V C , and interprotein S–S bonds are reductively cleaved as well, so dissociation of myosin II aggregates is observed in the high-V C regime. In addition, our work shows a V C -induced reversive structural transition in myosin II between α-helices and β-sheets.…”
Section: Discussionmentioning
confidence: 99%
“…Artificially reared Cyprinus carpio and Carassius auratus must be supplemented with VC to grow well. The GULO enzymatic activity in their livers is only 5%–10% that in Oreochroms mossambcus and Gadus morrhua , and 30% that in the mouse liver (Dabrowski, 1991; Ikeuci et al, 2007; Menezes et al, 2016). Our study showed that silkworm eggs, and fat bodies of larva and pupae show activity of the key enzyme GULO in the l ‐gulose pathway for synthesis of AsA, which catalyzes AsA production from l ‐gulonic acid‐γ‐lactone, thus further confirming that silkworms can synthesize AsA.…”
Section: Discussionmentioning
confidence: 99%